2011
DOI: 10.1093/abbs/gmr087
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Atorvastatin combined with adipose-derived mesenchymal stem cell transplantation on cardiac function in rats with acute myocardial infarction

Abstract: Mesenchymal stem cells (MSCs) have been extensively applied for the restoration of cardiomyocytes loss after acute myocardial infarction (AMI). However, the optimal therapeutic efficacy of MSCs in ischemic heart diseases has been hampered by their poor survival and low differentiated rates. Therefore, the improvement of MSC survival and differentiated rates is warranted and critical for the efficacy of MSCs in AMI. In this paper, MSCs isolated from rat inguinal fat tissues were termed as adiposederived mesench… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 26 publications
2
21
0
1
Order By: Relevance
“…For example, Cai et al . reported that in rats with acute myocardial infarction, atorvastatin therapy is beneficial for reducing inflammatory cytokine expression as well as decreasing leukocyte infiltration [10]. In addition, through improving endothelial function, statin therapy reduces leukocytes trans-endothelium migration, and the mechanism is associated with statins’ effect on inhibiting ROCK [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Cai et al . reported that in rats with acute myocardial infarction, atorvastatin therapy is beneficial for reducing inflammatory cytokine expression as well as decreasing leukocyte infiltration [10]. In addition, through improving endothelial function, statin therapy reduces leukocytes trans-endothelium migration, and the mechanism is associated with statins’ effect on inhibiting ROCK [15].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, induction of MI was performed as previously described by permanent ligation of the left anterior descending coronary artery with the help of ventilation (tidal volume, 6.0 ml; respiratory rate, 70 cycles/min) [10]. Thereafter, the surviving 37 rats were randomly divided into 4 groups as follows: atorvastatin group (10 mg/kg daily, oral gavage, n = 9), sitagliptin group (10 mg/kg daily, oral gavage, n = 9), combined group (10 mg/kg daily atorvastatin plus 10 mg/kg daily sitagliptin, n = 9), and control group (3 ml of normal saline daily, oral gavage, n = 10).…”
Section: Methodsmentioning
confidence: 99%
“…Existing evidence suggests that ischemia and hypoxia, inflammation, apoptosis, oxidative stress, and neuroendocrine activation together create a grim and adverse microenvironment in the infracted myocardium to threaten the survival of implanted stem cells [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27]. Clearly, maximizing the survival rate of transplanted cells is a critical step towards maximizing the potential of stem cell therapy for AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that combined therapy with mesenchymal stem cells (MSCs) and atorvastatin, a blood cholesterol-lowering agent, produces synergistic beneficial effects in the treatment of AMI, despite that neither atorvastatin nor MSCs can individually improve ventricular function significantly [15,16,17,18,19,20,21]. These findings retrieved the declining interest in applying and investigating stem cell therapy of AMI, and stirred up new surges for searching better strategies to boost MSCs therapy: combined MSCs therapy and pharmacotherapy is one of these proof-in-principle approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Il principale ostacolo al loro utilizzo è il tempo che impiegano per differenziarsi in cardiomiociti, circa 14 giorni, e la necessitĂ  prima della somministrazione di un trattamento che ne aumenti la resistenza all'ipossia e ai radicali liberi facilitando il loro attecchimento nella zona infartuata [50]. A questo scopo sono state messe in pratica diverse strategie, come la somministrazione di fattori di crescita (BMP, IGF-1, FGF) [51], di farmaci [52,53] (atorvastatina, estrogeni) o l'utilizzo di biomateriali come veicoli.…”
Section: Cellule Staminaliunclassified